From Ikhtilaf to Eklektisisme: Tracing Qodri Azizy's Evolutionary Perspectives on Islamic Legal Concepts - Nurdin, Nazar; Ridwan, Ridwan; Widianto, Eko (Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This article delves into and elucidates the framework of Qodri Azizy's Islamic legal thought as a prominent Muslim intellectual in Indonesia. His contemplations on eclecticism are deemed crucial in the context of national legal development, emerging from specific situations and contexts. The analysis employs normative and hermeneutical approaches, encompassing significant works such as